Proceedings of the 18th International Software Product Line Conference: Companion Volume for Workshops, Demonstrations and Tool 2014
DOI: 10.1145/2647908.2655972
|View full text |Cite
|
Sign up to set email alerts
|

An overview on analysis tools for software product lines

Abstract: A software product line is a set of different software products that share commonalities. For a selection of features, specialized products of one domain can be generated automatically from domain artifacts. However, analyses of software product lines need to handle a large number of products that can be exponential in the number of features. In the last decade, many approaches have been proposed to analyze software product lines efficiently. For some of these approaches tool support is available. Based on a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Open reading frames (ORF) were assembled based on the predicted reads of the metagenomic contigs using Bowtie2 (version 2.4.4). The KEGG (Kyoto Encyclopedia of Genes and Genomes) database was used to match the predicted metagenomic contigs . The counts of the functional genes were normalized using counts per million (CPM) measurements as follows: C P M = r e a d s m a p p e d t o g e n e s g e n e s e q u e n c e l e n g t h s u m o f ( r e a d s m a p p e d t o g e n e g e n e s e q u e n c e l e…”
Section: Methodsmentioning
confidence: 99%
“…Open reading frames (ORF) were assembled based on the predicted reads of the metagenomic contigs using Bowtie2 (version 2.4.4). The KEGG (Kyoto Encyclopedia of Genes and Genomes) database was used to match the predicted metagenomic contigs . The counts of the functional genes were normalized using counts per million (CPM) measurements as follows: C P M = r e a d s m a p p e d t o g e n e s g e n e s e q u e n c e l e n g t h s u m o f ( r e a d s m a p p e d t o g e n e g e n e s e q u e n c e l e…”
Section: Methodsmentioning
confidence: 99%
“…Recent surveys on product-line analyses give a detailed overview on related work [55] and related tools [37]. In particular, several analysis techniques are discussed, such as type checking, dataflow analyses, model checking, and theorem proving.…”
Section: Related Workmentioning
confidence: 99%
“…Thus it was noticed that properties concerning non-functionalities in software need to be considered as a primary factor in the developmental process. However, it was also observed that several software systems failed due to higher inadequacies in these properties [5]. Previous studies shows that non-functional part are treated as properties or traits of completed programming to be considered among software engineering researchers [6].…”
Section: Introductionmentioning
confidence: 99%